Testing The Antimicrobial Effectiveness of Manila Sauce Leaves (Manilkara Zapota L) against Bacteria Escherichia Coli: In Vitro Study - Azizah, Namirah Nurjiranah; Kartika, Irna Diyana; Hasbi, Berry Erida; Muchtar, Amrizal; Arsal, Andi St. Fahirah (Journal La Lifesci, 2024)
Diarrhea remains a significant public health concern globally, particularly affecting children under five years old. Traditional herbal remedies, including Manila Sapodilla (Manilkara zapota L) leaves, have been utilized in Indonesia for treating diarrhea due to their perceived efficacy and safety. This in vitro study aimed to assess the antimicrobial effectiveness of Manila Sapodilla leaf extract against Escherichia coli bacteria, a common cause of diarrhea. True experimental design was employed, utilizing various concentrations (25%, 50%, 75%, and 100%) of Manila Sapodilla leaf extract. The extract was obtained through maceration using ethanol followed by dilution with distilled water. Antimicrobial activity was evaluated using the Kirby-Bauer diffusion method, measuring inhibition zones formed around Escherichia coli colonies. Results demonstrated that Manila Sapodilla leaf extract exhibited inhibitory effects against Escherichia coli at all tested concentrations, albeit with varying degrees of effectiveness. The inhibition zones ranged from 5.37 mm to 8.53 mm, indicating resistance. Positive control using Ciprofloxacin displayed a significantly larger inhibition zone (21.75 mm), indicating sensitivity. These findings suggest the potential of Manila Sapodilla leaf extract as an alternative treatment for Escherichia coli infections. However, further research, including phytochemical analysis and exploration of different extraction methods and concentrations, is warranted to elucidate its therapeutic potential fully. This study contributes to the ongoing search for alternative herbal-based antibiotics to combat bacterial infections effectively.